Effect of selective inhibition of the p38 MAP kinase pathway on platelet aggregation - Kuliopulos, Athan; Mohanlal, Ramon; Covic, Lidija (Thrombosis and Haemostasis, 2004)
Systemic inflammation has been shown to be a contributing factor to the instability of atherosclerotic plaques in patients with acute coronary syndromes (ACS). VX-702, a novel p38 mitogen-activated protein kinase (MAPK) inhibitor, is currently under investigation in ACS patients with unstable angina to evaluate its safety and efficacy during percutaneous coronary intervention (PCI).The role of p38 MAPK in platelet aggregation of normal individuals was examined using the selective second generation p38 MAPK inhibitor VX-702. Treatment of platelets with thrombin (activates PAR1 and PAR4 thrombin receptors), SFLLRN (PAR1), AYPGKF (PAR4), collagen (α2β1 and GPVI/FCγIIR receptors) and U46619 (TXA2) resulted in strong activation of p38 MAPK. Activation of the GPIb von Willebrand factor receptor with ristocetin did not stimulate p38 MAPK. Pre-treatment of platelets with 1 μM VX-702 completely inhibited activation of p38 MAPK by thrombin, SFLLRN, AYPGKF, U46619, and collagen. There was no effect of VX-702 on platelet aggregation induced by any of the agonists in the presence or absence of aspirin, heparin or apyrase. It has been postulated that a potential role of p38 MAPK is to activate phospholipase A2 (cPLA2) which catalyses formation of arachidonic acid leading to production of thromboxane. Interestingly, we show contrasting effects of p38 MAPK inhibition as compared to aspirin inhibition on platelet aggregation in response to collagen. Blockade of TXA2 production by aspirin results in significant inhibition of collagen activation. However, VX-702 has no effect on collagen-mediated platelet aggregation, suggesting that blocking p38 MAPK does not effect thromboxane production in human platelets. Therefore, unlike aspirin blockade of thromboxane production in platelets, p38 MAPK inhibitors such as VX-702 do not significantly affect platelet function and would not be expected to contribute to an elevated risk of bleeding side-effects in treated patients.
Keywords: p38 MAPK; platelet function; aspirin